Efficient graphene saturable absorbers on D-shaped optical fiber for ultrashort pulse generation (2016)
ABSTRACT: We demonstrated a method to construct high efficiency saturable absorbers based on the evanescent light field interaction of CVD monolayer graphene deposited on side-polished D-shaped optical fiber. A set of samples was fabricated with two different core-graphene distances (0 and 1μm), covered with graphene ranging between 10 and 25mm length. The mode-locking was achieved and the best pulse duration was 256fs, the shortest pulse reported in the literature with CVD monolayer graphene in EDFL. As result, we find a criterion between the polarization relative extinction ratio in the samples and the pulse duration, which relates the better mode-locking performance with the higher polarization extinction ratio of the samples. This criterion also provides a better understanding of the graphene distributed saturable absorbers and their reproducible performance as optoelectronic devices for optical applications.